CHALLENGES AND PRACTICES IN FISCAL MANAGEMENT OF PUBLIC SCHOOLS TOWARDS A CAPACITY BUILDING PROGRA - Quinto, Ronald; Gaor, Mark Jeno (Journal of Governance and Public Administration, 2026)
This study examined the fiscal management challenges and practices among public elementary school heads in the Schools Division Office (SDO) of Bataan, Philippines, during Fiscal Year 2024, to inform a capacity-building program. A convergent parallel mixed-methods design was applied, assigning equal weight to quantitative and qualitative data. A stratified sample of 106 school heads completed a survey measuring challenges across four domains: budgeting, accounting, procurement, and asset management. The overall composite mean of 2.21 (“Slightly Challenging”) indicated general competency, with notable issues including excessive documentary requirements and unforeseen expenditures. Analysis of variance revealed significant differences in budgeting challenges by school size (p < .05) and accounting challenges by district (p < .05). Qualitative data from semi-structured interviews with 12 school heads yielded six thematic practices aligned under the HEROES Framework—Holistic Stewardship, Empowered Decision-Making, Resource Optimization, Organizational Transparency, Engagement of Stakeholders, and Sustained Capacity Development. Integrated analysis revealed a misalignment between principals’ ethical commitment and technical proficiency due to systemic barriers. The study recommends implementing the HEROES Capacity Development Program to enhance fiscal literacy, ensure policy compliance, and improve governance at the school level.